The hypermethylation of FOXP3 gene as an epigenetic marker for the identification of arsenic poisoning risk - Ma, Lu; Fang, Xiaolin; Zhang, Aihua (Human & experimental toxicology, 2022)
Background and Purpose: Arsenic exposure can lead to skin lesions and multiple organ damage, which are not easily reversible and for which there is no effective therapeutics. Identification of reliable epigenetic markers is essential for early recognition of arsenic poisoning risk. Anomalous DNA methylation of immune homeostasis regulator FOXP3 is a critical mechanism for triggering arsenic poisoning. This study aims to explore the value of FOXP3 methylation in the identification of arsenic poisoning risk. Methods: 88 arsenic poisoning subjects and 41 references were recruited. Urinary arsenic contents and FOXP3 methylation in PBLCs was measured by ICP-MS and pyrosequencing, respectively. Results: The results showed that the elevated FOXP3 methylation in PBLCs were associated with the increased levels of urinary arsenic and were positively associated with the increased risk of arsenic poisoning and its progression. The result of mediation analysis revealed that 24.3% of the effect of arsenic exposure on the risk of arsenic poisoning was mediated by increased FOXP3 methylation. Additionally, we constructed a nomogram model with FOXP3 methylation as an epigenetic predictor to assess the probability of individual arsenic poisoning. The model showed a robust ability in the discrimination of arsenic poisoning risk, with an area under receiver operating characteristics curve of 0.897(0.845–0.949) and more than 70% accuracy. The calibration curves and the Harrell concordance index showed that the consistency rate between the probability predicted by the nomogram model and the actual probability is 89.7%. Conclusions: Taken together, we found the great potential of FOXP3 methylation for the identification of arsenic poisoning risk and provided a new approach to the application of epigenetic markers in accurately quantifying the risk of adverse outcomes.